Intraoperative Analgesia with Magnesium Sulfate versus Remifentanil Guided by Plethysmographic Stress Index in Post-Bariatric Dermolipectomy: A Randomized Study - S. E. Silva Filho; S. Dainez; M. A. M. C. Gonzalez; F. Angelis; J. E. Vieira; C. S. Sandes (Anesthesiology Research and Practice)
Background. Magnesium sulfate reduces pain scores and analgesic consumption. Its use as an analgesic resource in opioid-free or opioid-sparing techniques have also been tested. The evaluation of the antinociceptive potency of drugs and doses indirectly, through hemodynamic oscillations has been questioned. A relatively new algorithm called the plethysmographic stress index has been considered sensitive and relatively specific as a parameter for assessing the need for intraoperative analgesia. Objectives. The aim of this trial was to assess the intraoperative analgesic capacity of magnesium sulfate compared to remifentanil. The secondary objectives were propofol consumption and its latency, the consumption of opioids, ephedrine, and cisatracurium. Patients and Methods. Forty patients scheduled for post-bariatric dermolipectomy were randomly assigned to two groups to receive total intravenous anesthesia with target-controlled hypnosis induced with propofol. Analgesia was obtained in the remifentanil group with remifentanil at an initial dose of 0.2 μg·kg−1·min−1 and in the magnesium sulfate group with magnesium sulfate 40 mg·kg−1 + 10 mg·kg−1·h−1. Results. There was no statistical hemodynamic difference between the groups before and after orotracheal intubation (p = 0.062) and before and after the surgical incision (p = 0.656). There was also no statistical difference in the variation of mean arterial pressure before and after intubation (p = 0.656) and before and after the surgical incision (p = 0.911). There was similar consumption of cisatracurium, ephedrine, and postoperative opioids between the groups. Some patients in the magnesium sulfate group needed more intraoperative fentanyl and propofol, although the latency of propofol was similar in both the groups. Conclusion. We conclude that using magnesium sulfate in intravenous general anesthesia for post-bariatric dermolipectomy is related to a significant reduction in opioid consumption without compromising hemodynamic stability. Overall, PSI monitoring was helpful in driving the analgesic strategy. The use of magnesium sulfate proved to be an important adjunct in the scenario presented, allowing the use of opioids to be avoided in certain cases. We found no statistical differences in the consumption of neuromuscular blocker and vasoconstrictor. Substituting opioids for magnesium sulfate leads to an increase in propofol consumption in the scenario presented. Studies with a larger sample are needed to corroborate the results presented and evaluate other potential advantages in reducing opioid consumption.